História natural de Leptodactylus fuscus (Schneider, 1799) no lavrado de Roraima (Amphibia : Anura : Leptodactylidae) - Azarak, Priscila Alencar (2012)
Leptodactylus fuscus is a small sized frog which lives in open areas and has a wide distribution, occurring from Panama to Argentina. In this study are presented information about the natural history of L. fuscus from two localities in savannas of Roraima. This study was conducted between february and july 2012, covering part of the dry period and the rainy period in Roraima. The morphometric differences in snout-vent length between adult males and females were significant. The morphological differences between the tympanic diameter of the males and females were significant. The reproductive pattern is of type prolonged during the rainy period. Males make underground burrows and they do attract females to perform spawning. The spawning is terrestrial and made in foam nest, near the banks of temporary puddles. The development of tadpole until metamorphosis takes up about 28 days in the field and 44 days in the laboratory. The spawnings were observed being preyed by snakes and insects. L. fuscus hunts waiting and was observed preying on earthworms (Anellida) and crickets (Orthoptera). In the analysis of stomach contents was found Orthoptera, Blattodea, Araneae, Hymenoptera, Coleoptera and Diptera. The spatial distribution of males and burrows was aggregated during the reproductive period.